Assessing Fluency and Coherence in the Speaking Skill Of Street Verdor in Tourism Area - Marzuki, M. Junaidi; Maysuroh, Siti; Ghina Athiyyaturrahmah (Mataram University, 2024)
Using the IELTS rubric as a method for evaluation, the study aims to determine assessing the present fluency and coherence levels among the chosen street vendors based on the criteria specified in the IELTS rubric. Through a qualitative research design, the data collected from a sample population consisting of 9 street vendors from Kuta Mandalika. In order to collect the data, the researcher through interview test which consist of two part, dialogue and monologue each part lasted up to 3-5 minutes. The result showed that there were 3 part category to determine which are intermediate, limited and not competent. The intermediate result show 2 people in range 5.5-6.5 Band. Limited shows 2 people in range 4-5 Band and the rest of them are not competent. In conclusions all the participants were within the context of the